2014
DOI: 10.1186/1475-2875-13-87
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of an automated RDT reader and data management device for Plasmodium falciparum/Plasmodium vivax malaria in endemic areas of Colombia

Abstract: BackgroundMassive implementation of malaria diagnostics in low-resource countries is regarded as a pivotal strategy in control and elimination efforts. Although malaria rapid diagnostic tests (RDTs) are considered a viable alternative, there are still obstacles to the widespread implementation of this strategy, such as reporting constraints and lack of proper quality assurance of RDT-based programmes at point-of-care (POC).MethodsA prospective cohort of patients, seeking routine care for febrile episodes at he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 31 publications
5
37
0
4
Order By: Relevance
“…La sensibilidad y especificidad de esta prueba oscilan entre 80-90%, independiente de la especie de Plasmodium [28]. Un estudio realizado en Colombia indica que a través de este método de microscopía, la sensibilidad es 93% y especificidad es 98,7% para P. falciparum, mientras que para P. vivax, la sensibilidad es 98% y la especificidad es 97, 9% [29]. Dentro de las dificultades que presenta este método es que solamente detecta parasitemias mayores a 50 parásitos/μL, y no permite detectar coinfecciones; esta incapacidad de detectar infecciones con baja carga de pará-sitos sanguíneos, conduce al no tratamiento de los pacientes y por ende al progreso de la enfermedad [30,31].…”
Section: Métodos Microscópicosunclassified
See 1 more Smart Citation
“…La sensibilidad y especificidad de esta prueba oscilan entre 80-90%, independiente de la especie de Plasmodium [28]. Un estudio realizado en Colombia indica que a través de este método de microscopía, la sensibilidad es 93% y especificidad es 98,7% para P. falciparum, mientras que para P. vivax, la sensibilidad es 98% y la especificidad es 97, 9% [29]. Dentro de las dificultades que presenta este método es que solamente detecta parasitemias mayores a 50 parásitos/μL, y no permite detectar coinfecciones; esta incapacidad de detectar infecciones con baja carga de pará-sitos sanguíneos, conduce al no tratamiento de los pacientes y por ende al progreso de la enfermedad [30,31].…”
Section: Métodos Microscópicosunclassified
“…Presenta una sensibilidad similar a la gota gruesa, de un 95% con 100 parásitos/μL en el caso de P. falciparum. Un estudio realizado en Colombia, identificó que la especificidad de PDR en el diagnóstico de malaria por P. falciparum es 99% y por P. vivax es 98,5% [29].…”
Section: Las Pruebas De Diagnóstico Rápido (Pdr)unclassified
“…Similarly, studies on other diseases, such as malaria, have shown high concordance between visual and device interpretation (N98%), as well as the potential benefits of quality assurance, automated data transmission, and health system strengthening [11].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…1) [11]. Automated data transmission could also reduce the potential for human error in data capture and surveillance.…”
Section: Automating Real-time Surveillancementioning
confidence: 99%
See 1 more Smart Citation